2020
DOI: 10.1002/elan.202060137
|View full text |Cite
|
Sign up to set email alerts
|

Novel Type of Carbon Nanotube Paste Electrode Modified by Sb2O3 for Square Wave Anodic Stripping Voltammetric Determination of Cd2+ and Pb2+

Abstract: A novel type of carbon paste electrode modified by multi-walled carbon nanotubes and antimony trioxide (Sb 2 O 3 /CNTCPE) was applied for square wave anodic stripping voltammetry (SWASV) of Cd 2 + and Pb 2 +. Important parameters (deposition potential, deposition time, HCl concentration) were optimized and linear concentration dependence was obtained in the range of 10-100 ppb with LOD 1.7 ppb for Cd 2 + and 1.2 ppb for Pb 2 +. The practical applicability was tested on the determination of Cd 2 + and Pb 2 + in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…As an electrolyte, a 0.01 M HCl solution was used to detect Pb and Cd ions in water samples. The comparison of the new method with GFAAS (graphite furnace atomic absorption spectroscopy) in real samples, revealed that the new SWASV method for the determination of Cd 2+ and Pb 2+ ions is free of systematic errors and gave low detection limits equal to 1.2 μg/L and 1.7 μg/L respectively [29]. A lithographically printed black carbon electrode has also been molded with poly(propyleneimine) (SPE-CB-PPI) creating a sensitive sensor with low limits of detection (3.6 μg/L, 15.3 μg/L) in the determination of Pb and Cd metals in water samples, amplified by the 0.1 M acetate buffer electrolyte and pH 4.6 [30].…”
Section: Simultaneous Determination Of Pb and CDmentioning
confidence: 99%
“…As an electrolyte, a 0.01 M HCl solution was used to detect Pb and Cd ions in water samples. The comparison of the new method with GFAAS (graphite furnace atomic absorption spectroscopy) in real samples, revealed that the new SWASV method for the determination of Cd 2+ and Pb 2+ ions is free of systematic errors and gave low detection limits equal to 1.2 μg/L and 1.7 μg/L respectively [29]. A lithographically printed black carbon electrode has also been molded with poly(propyleneimine) (SPE-CB-PPI) creating a sensitive sensor with low limits of detection (3.6 μg/L, 15.3 μg/L) in the determination of Pb and Cd metals in water samples, amplified by the 0.1 M acetate buffer electrolyte and pH 4.6 [30].…”
Section: Simultaneous Determination Of Pb and CDmentioning
confidence: 99%